2009
DOI: 10.1542/peds.2008-1578h
|View full text |Cite
|
Sign up to set email alerts
|

General Pediatrics Resident Perspectives on Training Decisions and Career Choice

Abstract: OBJECTIVE. Little is known regarding at what point during the training period residents in pediatrics make decisions on their future career choices. As part of a dedicated process of reexamining the structure of residency training in pediatrics, the American Board of Pediatrics sought information to better understand the influences, process, and sequencing of both residency program selection and career decision-making among residents.METHODS. All pediatrics resident physicians in all training programs in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 17 publications
6
50
0
1
Order By: Relevance
“…These findings are similar to those of previous Canadian studies (Macnab et al 1998;Veale et al 1999 Validating paediatric objectives and training e141 multiple other US studies (Camp et al 1997;Roberts et al 1997;Mulvey et al 2000;Blumenthal et al 2001;Blendon et al 2002;Garfunkel et al 2005;Freed et al 2009aFreed et al , 2009bFreed et al , 2009cFreed et al , 2009dLeslie 2009). Lieberman and Hilliard (2006) found that paediatricians certified in Canada between 1999 and 2003 had received excellent training in most paediatric subspecialties and felt adequately prepared for their careers.…”
Section: Competencies Rated As Less Than Adequately Preparedsupporting
confidence: 90%
“…These findings are similar to those of previous Canadian studies (Macnab et al 1998;Veale et al 1999 Validating paediatric objectives and training e141 multiple other US studies (Camp et al 1997;Roberts et al 1997;Mulvey et al 2000;Blumenthal et al 2001;Blendon et al 2002;Garfunkel et al 2005;Freed et al 2009aFreed et al , 2009bFreed et al , 2009cFreed et al , 2009dLeslie 2009). Lieberman and Hilliard (2006) found that paediatricians certified in Canada between 1999 and 2003 had received excellent training in most paediatric subspecialties and felt adequately prepared for their careers.…”
Section: Competencies Rated As Less Than Adequately Preparedsupporting
confidence: 90%
“…Only 29% of third-year residents who intend to practice general pediatrics, just 13% of all third-year residents, plan to practice general pediatrics in both ambulatory and hospital settings. 5 This is a different situation from the one for which residency education was intended.…”
Section: Innovation In Residency Education and Evolving Pediatric Heamentioning
confidence: 99%
“…10 It must come to terms with increasing dichotomization of care and careers. 4,5 It must embrace the paradox of accommodating both breadth and career-specific learning. Residents who have made career choices should have access to concentrated, longitudinal learning opportunities that go well beyond continuity clinics.…”
Section: Innovation In Residency Education and Evolving Pediatric Heamentioning
confidence: 99%
“…Males, international medical school graduates (IMGs), and residents from larger residency programs are more likely to undertake subspecialty training. [1][2][3][4] Other related factors include market forces, indebtedness, mentor specialty, and work hours or the availability of part-time positions. [3][4][5][6] Published research has directly asked pediatricians what led them to pursue or not pursue subspecialty training.…”
mentioning
confidence: 99%
“…Surveys of pediatric residents and early career pediatricians found structured hours and lifestyle were important factors to those who planned to pursue a career in general pediatrics. 2,7 Interest in specific diseases and patient populations remained the most important factor in post-residency career choice for those residents planning to pursue fellowships. 8,9 In the current study, our goal is to learn more about what happens in the work and life of pediatricians after fellowship.…”
mentioning
confidence: 99%